IMPLEMENTATION OF HOTEL REVENUE MANAGEMENT STRATEGIES DURING A MARTIAL LAW - Anatolii Mazaraki; Mariia Kulyk; Margaryta Boiko; Myroslava Bosovska; Nadiia Vedmid (Agora International Journal of Economical Sciences (AIJES), 2024)
The Hotel Revenue Management strategy is used to measure the future occupancy, ADR, REVPAR, TREVPAR. Prices impact on the further development of business models implemented by the hotels is analysed. The purpose of this study is to determine the influence of Revenue Management Strategy on KPI and Revenue indicators at hotels in Ukraine. The research method used is a quantitative descriptive research method. The study used a sample of 12 respondents with 8 statements. Data were collected by observing participants, reviewing company documents, and seeking input from key informants. In crisis conditions, in particular caused by martial law in Ukraine, hotels reorient themselves to new segments, study needs and adapt services to new security requirements. One of the ways to increase efficiency and occupancy can be revenue management strategies adapted to crisis or post-crisis situations. We have proposed a typology of income management strategies adapted to new conditions.
Keywords: 330